Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 1 - Some Basic Concepts of Arithmetic and Algebra - Chapter 1 Review Problem Set: 66

Answer

$-32$

Work Step by Step

Substituting $x= -4 ,$ the given expression, $ 2(x-1)-(x+2)+3(x-4) ,$ evaluates to \begin{array}{l}\require{cancel} 2(-4-1)-(-4+2)+3(-4-4) \\\\= 2(-5)-(-2)+3(-8) \\\\= -10+2-24 \\\\= -8-24 \\\\= -32 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.